Pharmacological doses of melatonin induce alterations in mitochondrial mass and potential, bcl‐2 levels and K+ currents in UVB‐exposed U937 cells. (30th January 2013) - Canonico, Barbara; Luchetti, Francesca; Ambrogini, Patrizia; Arcangeletti, Marcella; Betti, Michele; Cesarini, Erica; Lattanzi, Davide; Ciuffoli, Stefano; Palma, Fulvio; Cuppini, Riccardo; Papa, Stefano
Abstract: Apoptosis is observed in 'actively' dying cells after the exposure to cell stressors such as ultraviolet light irradiation. Since melatonin has been proposed to act under stressful conditions as cell protection factor, in this study we examined the potential of this molecule when used at pharmacological concentrations to control mitochondrial damage and apoptotic signalling of UVB irradiated U937 human leukaemic cells. Moreover, the effect of melatonin treatment on electrophysiological properties and membrane K + currents of irradiated U937 cells was investigated as functional aspects relevant to the anti‐apoptotic role of melatonin. The general effect is associated with the restoration of mass, number and membrane potential of mitochondria, with a lower caspase activation and bcl‐2 upregulation. In the presence of the caspase inhibitor ZVAD‐Fmk, melatonin seems to drive UVB stressed cells to follow the mitochondrial intrinsic pathway, interfering just at the mitochondrial level. Moreover, treatment with melatonin, as well as ZVAD‐Fmk, prevented the K + current reduction observed late following the UVB insult application, by sparing cells from death; this result also indicates that the decrease of K + leakage currents could represent a functional feature of apoptotic process in UV‐exposed U937 cells.